The eco-friendly spectrophotometric methods for duloxetine and amitriptyline quantification using eosin Y: content uniformity and greenness evaluation - Al Amir S. Zaafan; Hadeer A. Elhamdy (BMC Chemistry)
Abstract Straightforward, eco-friendly, quick, and sensitive spectrophotometric procedures were created and proven to be effective for determining the amount of duloxetine and amitriptyline in bulk and pharmaceutical dosage forms. The basis of the suggested procedures was the formation of an ion association complex in an aqueous buffered solution containing duloxetine and amitriptyline with eosin Y. The resulting compound displayed absorption peaks at 546 nm under optimum circumstances. With a linear relationship and a good correlation value of 0.9996 for DLX and 0.9997 for AMT, the calibration plots were rectilinear over the concentration range of 0.5–8 µg mL− 1 for DLX and 1–7 µg mL− 1 for AMT. The quantitation limits were 0.48 and 0.49 µg mL− 1 for DLX and AMT, respectively, whereas the detection limits were 0.16 µg mL− 1 for both drugs. The research process has been optimized with respect to the many experimental parameters. The approaches were assessed in accordance with ICH guidelines. The suggested approaches were successfully used to analyze pharmaceutical formulations, including the cited medications. Additionally, the recommended methods performed admirably when used to assess content uniformity. The proposed method is highly green as water was used as the solvent. Utilizing four metric tools called the NEMI, Eco-Scale, GAPI, and AGREE, the established techniques’ environmental impact was assessed. Also, the practicality (blueness) of procedures was assessed using a recently developed metric called the Blue Applicability Grade Index (BAGI).